Pengembangan Bahan Ajar (Buku) Ekonometrika Berbasis Media Pembelajaran Aplikasi Website (Studi Kasus Pada Prodi Pendidikan Ekonomi Universitas Negeri Medan) - Putri Sari M J Silaban; Joko Suharianto; Aurora Elise Putriku; Sabda D.N. Siahaan; Jessica Putri Br. Sembiring (Cetta: Jurnal Ilmu Pendidikan, 2022)
One form of offline learning transformations to the online is the conversion of the printing materials to web-based teaching materials. The hope is to facilitate and support the management of online learning. In general, the study aims to know the degree of worth and effectiveness of the teaching material in economic educationists can improve students' learning. It uses addie models. The study was done on student students of class a v-semester who took the economics course at prodi economic education in 2021/2022. For a small test sample taken 30 students. The effectiveness of test results concludes that students' learning after the use of economic etrica is higher than those of pretest students. This is significant if the teacher-based website on the resulting econometrical courses proves to be effective in improving student studies.